Efficiency Comparison between Conventional and Islamic Rural Banks in Sumatra during the COVID-19 Pandemic - Akbar, Nashr; Ikhwan, Ihsanul; Riani, Ririn (Universitas Islam Internasional Indonesia, 2023)
This study aims to examine and compare the efficiency of conventional rural banks and Islamic rural banks in their roles as intermediary institutions during the COVID-19 pandemic in Sumatra, Indonesia. Furthermore, the efficiency determinants were further analysed to find some variables that affect rural banks’ efficiency. Non-Parametric approach, Data Envelopment Analysis (DEA), and Tobit Regression are employed in this study. The results show that Islamic rural banks have better efficiency performance compared to conventional rural banks, but that there is a fluctuating efficiency trend experienced by both types of rural banks during the observation period. In addition, the potential improvement result indicates that financing and operating revenue variables are the main causes of rural bank inefficiency. Furthermore, the Tobit Regression result finds that capital and bank size significantly improve the efficiency level, but that risk significantly reduces bank efficiency.